2015
DOI: 10.5966/sctm.2014-0272
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Macrophages: Versatile Gatekeepers During Pancreatic β-Cell Development, Injury, and Regeneration

Abstract: Macrophages are classically considered detrimental for pancreatic b-cell survival and function, thereby contributing to b-cell failure in both type 1 (T1D) and 2 (T2D) diabetes mellitus. In addition, adipose tissue macrophages negatively influence peripheral insulin signaling and promote obesityinduced insulin resistance in T2D. In contrast, recent data unexpectedly uncovered that macrophages are not only able to protect b cells during pancreatitis but also to orchestrate b-cell proliferation and regeneration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 87 publications
2
34
0
Order By: Relevance
“…Cancers of the endocrine cells of the pancreas or pancreatic neuroendocrine tumors (PanNET) are less common and will not be discussed in this review[107,108]. Macrophages play an important role in pancreatic cancer as well as in other diseases of the pancreas[104]. Indeed, TAM have been shown to be present in pancreatic cancer in all of its stages, starting from the preinvasive stage and persisting throughout progression[109].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Cancers of the endocrine cells of the pancreas or pancreatic neuroendocrine tumors (PanNET) are less common and will not be discussed in this review[107,108]. Macrophages play an important role in pancreatic cancer as well as in other diseases of the pancreas[104]. Indeed, TAM have been shown to be present in pancreatic cancer in all of its stages, starting from the preinvasive stage and persisting throughout progression[109].…”
mentioning
confidence: 98%
“…Comparing op/+ and op/op mice, which lack M-CSF, it was demonstrated that M-CSF-dependent macrophages are essential for full insulin-producing cell mass development and postnatalislet morphogenesis[101,102]. Recently, steady-state tissue resident pancreatic macrophages were reported to consist of two main subsets which can be discerned based on a differential MHC class II expression level -the MHC-II lo and the more prominent MHC-II hi macrophages -, and which are more M2-or M1-like polarized, respectively[103,104]. Notably, these pancreatic macrophage populations show several similarities to the MHC-II lo and MHC-II hi TAM subsets that were originally identified in breast and lung cancer models[54,85,89].…”
mentioning
confidence: 99%
“…Tissue-resident macrophages rather than monocyte-derived ones produced beta cell mitogens. Continued research on macrophage function in pancreas may thus uncover the mechanisms underlying their roles in beta cell protection during pancreatitis, the enhancement of beta cell activity and their contribution to the control of beta cell proliferation and regeneration following beta cell injury (reviewed in [21]). The identification and characterisation of macrophage subtypes and their secretome might contribute to the development of new therapeutic strategies for diabetes.…”
Section: Partial Duct Ligation To Identify Cells and Signals For Betamentioning
confidence: 99%
“…In contrast, M2 macrophages are considered to be critical effector cells in the resolution of inflammation and the promotion of tissue repair [19,20]. Emerging evidence has demonstrated a role of M2 macrophages during β-cell protection, repair, and regeneration [21][22][23]. Xiao et al [24] found that M2 macrophages induced β-cell proliferation after pancreatic duct ligation and that depleting pancreatic macrophages with clodronate led to decreased β-cell replication.…”
Section: Introductionmentioning
confidence: 99%